Compact self-Q-switched Tm:YLF laser at 1.91 μm. (1st March 2018) - Zhang, B.; Li, L.; He, C.J.; Tian, F.J.; Yang, X.T.; Cui, J.H.; Zhang, J.Z.; Sun, W.M.
Highlights: First demonstration of compact self-Q-switched Tm:YLF laser. Robust self-Q-switched pulse output is obtained at 1.91 μm in fundamental mode. Average output power and pulse energy are as high as 610 mW and 29 μJ. Self-Q-switching dynamics is explained through saturable re-absorption mechanism. Abstract: We report self-Q-switching operation in a diode-pumped Tm:YLF bulk laser by exploiting saturable re-absorption under the quasi-three-level regime. Robust self-Q-switched pulse output at 1.91 μm in fundamental mode is demonstrated experimentally with 1.5 at.% doped Tm:YLF crystal. At maximum absorbed pump power of 4.5 W, the average output power and pulse energy are obtained as high as 610 mW and 29 μJ, respectively, with the corresponding slope efficiency of 22%. Pulse repetition rate is tunable in the range of 3–21 kHz with changing the pump power. The dynamics of self-Q-switching of Tm:YLF laser are discussed with the help of a rate equation model showing good agreement with the experiment. The compact self-Q-switched laser near 2 μm has potential application in laser radar systems for accurate wind velocity measurements.